P007 GAPS IN COMMUNICATION BETWEEN PATIENTS WITH ULCERATIVE COLITIS AND HEALTHCARE PROVIDERS: RESULTS OF A GLOBAL ULCERATIVE COLITIS NARRATIVE SURVEY. (7th February 2019) - Rubin, David T; Hart, Ailsa; Kayhan, Cem; Rubin, Michele; Dubinsky, Marla; Keefer, Laurie; Melmed, Gil; Colombel, Jean-Frederic; Schreiber, Stefan
Abstract: Objective: The Ulcerative Colitis (UC) Narrative is a global survey of patients (pts) and gastroenterology physicians (GIs) aimed at identifying the impact of UC and comparing and contrasting perceptions of UC burden and management approaches. Here, we present data from 2100 pts and 1254 GIs in Australia, Canada, Finland, France, Germany, Italy, Japan, Spain, the UK, and the USA. Methods: Surveys were conducted online and by phone by The Harris Poll between August 2017 and February 2018. Eligible adult pts with UC (confirmed by endoscopy) were those who had visited a GI in the previous 12 months and had ever received prescription medication. Self-reported medication history was used as a proxy for disease severity, with pts with moderate to severe UC defined as pts who had ever taken immunosuppressants, tumor necrosis factor inhibitors, other biologics, or corticosteroids for >4 of the past 12 months. Pts who had only ever taken 5-aminosalicylates or had a colectomy were excluded. Eligible GIs were those who saw ≥10 UC pts each month (≥5 in Japan), of whom ≥10% were taking a biologic and did not practice in a long-term care facility or hospice. Data are presented from all respondents who consented and completed the survey. Results: The UC pt sample was 53% male, and 82% (n=1731) had moderate to severe UC; 67% (n=1415) described their UC to be controlled with few to no symptoms. Pt characteristics are summarized in the Table. GIs had been in specialty practice for a mean of 16.4 (standard deviation 8.35) years and saw a mean of 40 pts with UC each month. Overall, only 30% of pts were very satisfied with their current treatment, in comparison to GIs' mean estimation of 43% of pts to be somewhat satisfied. In total, approximately three-quarters of pts (76%) wished they had more medication choices to treat their UC. Approximately half of pts (54%) wished that their GI had discussed all available treatment options with them earlier so they had a better idea of their choices, and 74% of GIs wished that they had more time to do so. The top two indicators for considering changing medications were similar for pts and GIs: continued flares (45% of pts; 60% of GIs) and continued symptoms (34% of pts; 53% of GIs). Conclusion: In this global survey, most pts were not very satisfied with their current treatment, and expressed a desire for greater medication choices. Pts and GIs were in agreement regarding the symptoms leading to the consideration of changes in medication, suggesting that these symptoms are central to optimizing UC management. These findings suggest that time should be allowed to discuss UC treatment options earlier during the course of disease in order to improve the experience of both pts and GIs.